Rice farming in central Java, Indonesia-Adoption of sustainable farming practices, impacts and implications - Connor, Melanie; de Guia, Annalyn H.; Pustika, Arlyna Budi; Sudarmaji; Kobarsih, Mahargono; Hellin, Jon (MDPI, 2021)
Farmer adoption of sustainable rice farming technologies and practices is critical for climate change adaptation and mitigation. Often adoption is investigated in isolation focusing on factors influencing farmer decision making and overlooking the effects of technology adoption on farmers’ livelihoods and perceptions of change. Therefore, the present study investigated technology adoption and its effects on farmers with a special focus on additional revenue allocation and perception of social, economic and environmental change. Using a digital survey platform, 153 farmers (21.6% female) were interviewed in three sub-districts of Yogyakarta, Indonesia. On average, farmers adopted two technologies or practices, adopted high-yielding rice varieties, and increased their revenue from US$105 to US$122 per hectare per season. Barriers to adoption included time constraints, unsuitability for field conditions and incompatibility with cropping systems. Farmers invested the extra income in farming business and improved diets. Furthermore, farmers perceived changes in social and human capital and also poverty reduction due to technology adoption. This study highlights the importance of including an analysis of social impact in agricultural research.